ANALISIS FAKTOR YANG MEMPENGARUHI KUALITAS PRODUKSI ASI PADA IBU MENYUSUI TAHUN 2024 - Yayuk Sri Rahayu; Rina Dwi Anggraeni; Dewi Rubi Fitriani (Journal of Innovation Research and Knowledge, 2024)
Breast milk is the best food that a mother can give to her baby. Breast milk alone is enough to meet the needs of babies up to 6 months of age. The components of breast milk, both micronutrients and macronutrients, are very important to determine the quality of breast milk provided by breastfeeding mothers to their babies. The purpose of this study is to find out the factors that affect the quality of breast milk production in breastfeeding mothers in 2023. The research design uses a cross-sectional study with 25 respondents. The analysis used univariate and bivariate. The results showed that the factors of Husband Support, Caregiver Support, Workplace Support, and Health Worker Support were related to exclusive breastfeeding. The p value < 0.05 means that there is a relationship with the Quality of Breast Milk Production in Breastfeeding Mothers. In conclusion, there is a relationship between husband support, caregiver support, workplace support, health care support and breast milk production